Proceedings of the International Symposium “Engineering and Earth Sciences: Applied and Fundamental Research” (ISEES 2018) 2018
DOI: 10.2991/isees-18.2018.19
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in Tissues of Red Fox as Indicator of Environmental Pollution

Abstract: Twenty-three red foxes (Vulpes vulpes L.) were tested for the presence of mercury in their internal organs. These animals were captured in the Vologda region (Northwest Russia) within 2009 and 2018. The animal's liver, kidneys, muscles, brain, spleen, chyme and intestinal wall were tested. The concentrations level ranged between 0.001 mg/kg of wet mass in the chyme and the brain-up to 0.713 mg/kg of wet mass in kidneys. There is a strong correlation between the concentrations of mercury in separate pairs of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The US Environmental Protection Agency (US EPA) has established recommended levels of mercury in hair (<1 mg/kg), which correspond to the reference intake dose (RFD) of 0.1 mkg/kg of body weight per day [5]. The accumulation of mercury in biotic and abiotic components of biosystems has been studied in the Vologda region for the last decades [6][7][8]. On the territory of the Vologda region, the content of mercury in hair was studied only in one coastal Kirillovsky district and the industrial city of Cherepovets [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The US Environmental Protection Agency (US EPA) has established recommended levels of mercury in hair (<1 mg/kg), which correspond to the reference intake dose (RFD) of 0.1 mkg/kg of body weight per day [5]. The accumulation of mercury in biotic and abiotic components of biosystems has been studied in the Vologda region for the last decades [6][7][8]. On the territory of the Vologda region, the content of mercury in hair was studied only in one coastal Kirillovsky district and the industrial city of Cherepovets [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of mercury in amphibians and the way it is stored inside their organisms are insufficiently studied, presently despite the fact that amphibians play a unique role in ecosystems, connecting the aquatic and terrestrial biocycles. Previous studies have demonstrated unequal accumulation of mercury in mammals from different parts of the Vologda region territory [9], [10]. At the same time, high concentrations of mercury in perch muscles (>0.5 mg HG/kg) have been repeatedly found in fish from lakes of the Vologda region [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%